Rise against rumors: Leveraging online social movements for hoax prevention by netizens - Anwar, Rully Khairul; Khadijah, Ute Lies Siti; Rizal, Edwin (Jurnal Kajian Komunikasi, 2023)
Background: Misinformation and harmful content spread on social media have sparked the anti-hoax movement. This research examines the motivations and participation of network users in combating hoaxes on digital platforms. Further investigation is required to examine the impact of framing, collective identity, and action factors on the propensity of netizens to actively engage in combating online hoaxes. Purpose: This study focused on framing, collective identity, and action components to explore the motivations behind netizens’ involvement in the anti-hoax movement on social media. Methods: In this study, web scraping, surveys, and netnographic techniques were employed to examine the motivations and trends of participation in the anti-hoax campaign. Data were collected from active members of MAFINDO on Facebook to facilitate this investigation. Results: Social media platforms, like those that MAFINDO uses, offer significant spaces for empowering and mobilizing communities to counteract false information and harmful content. The intentional construction of the anti-hoax movement, the establishment of a collective identity, and the alignment with the values of internet users were crucial elements in driving active engagement. The community employed efficacious tactics to counteract misinformation, such as verifying facts and presenting opposing viewpoints. These findings demonstrate the efficacy of social media platforms in resolving online problems. Conclusion: The effectiveness of the anti-hoax campaign hinges on factors like framing, collective identity, and agency that inspire internet users to engage and tackle the challenges of misinformation on social media. Implications: This study emphasizes how social media plays a key role in mobilizing internet users to fight hoaxes through effective framing, shared identity, and customized action factors.